Trans-Acting Effectors Versus RNA Cis-Elements: A Tightly Knit Regulatory Mesh - Carrier, Marie-Claude; Ng Kwan Lim, Evelyne; Jeannotte, Gabriel; Massé, Eric (Frontiers in Microbiology, 2020)
Prokaryotic organisms often react instantly to environmental variations to ensure their survival. They can achieve this by rapidly and specifically modulating translation, the critical step of protein synthesis. The translation machinery responds to an array of cis-acting elements, located on the RNA transcript, which dictate the fate of mRNAs. These cis-encoded elements, such as RNA structures or sequence motifs, interact with a variety of regulators, among them small regulatory RNAs. These sRNAs are especially effective at modulating translation initiation through their interaction with cis-encoded mRNA elements. Here, through selected examples of canonical and non-canonical regulatory events, we demonstrate the intimate connection between mRNA cis-encoded features and sRNA-dependent regulation. We also address how sRNA-based mechanistic studies can drive the discovery of new roles for cis-elements. Finally, we briefly overview the challenges of using translation regulation by synthetic regulators as a tool.